Деревянный мост коробчато-балочной конструкции с применением клееных элементов - Новик, С. В.; Костюкович, О. В. (БНТУ, 2017)
In the article a box-beam bridge structure made using glued beams is examined. The technological process of construction is described. On the basis of the conducted research the conclusion about profitability glued wooden designs in modern bridge construction application is made.